2013
DOI: 10.1111/jore.12023
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Justice and Mercy

Abstract: The concept of forgiveness is analyzed as a moral gesture toward the offender designed to help restore that individual's moral standing. Jewish sources on the conditions under which forgiveness is obligatory are explored and two contrasting positions are presented: one in which the obligation to forgive is conditional on the repentance of the offender and another in which people are required to forgive unconditionally. These two positions are shown to represent different ways of framing the offending behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…People vary significantly from each other in terms of how they assess a certain transgression (Newman, 1987). Hu et al (2018) used two different scandals to represent a minor and a major transgression respectively through experimental manipulation, while different individuals may view the same transgression as having different degrees of severity.…”
Section: Celebrities' Infidelity and Audiences' Romantic Beliefsmentioning
confidence: 99%
“…People vary significantly from each other in terms of how they assess a certain transgression (Newman, 1987). Hu et al (2018) used two different scandals to represent a minor and a major transgression respectively through experimental manipulation, while different individuals may view the same transgression as having different degrees of severity.…”
Section: Celebrities' Infidelity and Audiences' Romantic Beliefsmentioning
confidence: 99%
“…Existing literature posits that school psychologists exhibit a greater number of stressors than their counterparts in counseling and clinical psychologists (Huebner, 1993; Newman, 2013), however, to date, no known study has examined the relationship between perceived stress and psychological well-being in school psychology graduate students. Hence this study was a unique, timely, and important investigation of self-care practices and resulting outcomes within school psychology graduate students across Canada to aid in the development of training programs, the promotion of healthier graduate school cultures, and increasing productivity in those training to become school psychologists.…”
Section: Relevance To the Practice Of School Psychologymentioning
confidence: 99%
“…It is particularly important to address school psychologists’ self-care as research (Huebner, 1993; Newman, 2013) has indicated that school psychologists, in comparison to clinical, and counseling psychologists, are more susceptible to burnout, due to higher levels of emotional exhaustion (i.e., feeling overwhelmed by job demands), depersonalization (i.e., developing negative attitudes toward clients), decreased levels of personal accomplishment (i.e., feeling incompetent and ill-equipped to support clients), lack of experience, and increased interpersonal relationships (Badali & Habra, 2003; Daly & Gardner, 2022). These findings could be attributed to the vast array of challenges and expectations school psychologists are faced with daily (Fagan & Wise, 2000).…”
Section: School Psychologists’ Self-carementioning
confidence: 99%
“…This sequence may be possible because, for example, various faith traditions require the faithful to forgive others – to, in effect, turn the other cheek , in order to lay claim upon ‘divine’ forgiveness. For such religious devotees, giving forgiveness in the aftermath of wrongdoing is considered an ethical obligation and a religious duty to God (Newman, 1987). It could be argued that a religious construction of forgiveness would predispose victims to forgive even without an offender’s apology.…”
Section: Key Elements and Impediments Of Apology–forgiveness Cycle In...mentioning
confidence: 99%